Micro-mechanical evaluations of adhesion properties for Cr-coated accident tolerant fuel cladding - Jong-Dae Hong; Hongryul Oh; Daehyeok Ahn; Dongchan Jang; Hyun-Gil Kim; JaeYong Kim; Hyochan Kim; Martin Ševeček (Nuclear Materials and Energy)
The development of accident tolerant fuel (ATF) cladding has been encouraged to satisfy increased nuclear safety demands under accident conditions since Fukushima accident. Coating techniques using oxidation-resistant materials, such as Cr and Al, on existing Zr-alloy claddings have been widely applied as short-term solutions. However, coating delamination due to poor adhesion may reduce its benefits, such as low waterside corrosion/oxidation rates and fretting resistance, which necessitates accurate evaluation of coating adhesion suitability. In this study, micro-mechanical tests, micro-cantilever bending test and surface and interfacial cutting analysis system test, were conducted to qualitatively and quantitatively evaluate adhesion properties on a coated ATF cladding. In situ scanning electron microscopy-based micro-cantilever bending tests were performed using a pico-indenter equipped with a diamond flat tip. We present the results for magnetron-sputtered Cr-coated ATF claddings in detail. Micro-cantilever tests on the Cr-Zr interface revealed that deformation and failure primarily occurred in the Zr substrate, rather than at the interface. And the Cr-coated cladding showed highly adherent mechanical bonds, as evidenced by the interfacial strength and elastic modulus. SAICAS tests confirmed that peeling of the coating layer occurred only when the applied force exceeded the cutting force of the coating layer. The experimental results suggest that the Cr-coated cladding exhibited a sufficiently adherent mechanical bond to prevent delamination of the coating.